2020
DOI: 10.3390/jcm9051251
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulations of MicroRNA and Gene Expression in Chronic Venous Disease

Abstract: Chronic venous disease (CVD) is a vascular disease of lower limbs with high prevalence worldwide. Pathologic features include varicose veins, venous valves dysfunction and skin ulceration resulting from dysfunction of cell proliferation, apoptosis and angiogenesis. These processes are partly regulated by microRNA (miRNA)-dependent modulation of gene expression, pointing to miRNA as a potentially important target in diagnosis and therapy of CVD progression. The aim of the study was to analyze alterations of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 94 publications
(107 reference statements)
0
27
0
Order By: Relevance
“…Another miRNA negatively correlated with cholesterol, miR-374a-5p, is able to regulate the expression of many target genes involved in carbohydrates and lipids biosynthesis and inflammation, particularly interleukin-17A, in turn, involved in lipid metabolism ( Yu et al, 2014 ; Doumatey et al, 2018 ). Also, miR-1277-5p and miR-1273c have been reported as altered in inflammatory statuses ( Zalewski et al, 2020 ). Altogether, the observed anti-correlations between cholesterol intake and these miRNAs suggest that cholesterol itself could participate in the regulation of its efflux in macrophages, as recently reported for HDL ( Orekhov et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another miRNA negatively correlated with cholesterol, miR-374a-5p, is able to regulate the expression of many target genes involved in carbohydrates and lipids biosynthesis and inflammation, particularly interleukin-17A, in turn, involved in lipid metabolism ( Yu et al, 2014 ; Doumatey et al, 2018 ). Also, miR-1277-5p and miR-1273c have been reported as altered in inflammatory statuses ( Zalewski et al, 2020 ). Altogether, the observed anti-correlations between cholesterol intake and these miRNAs suggest that cholesterol itself could participate in the regulation of its efflux in macrophages, as recently reported for HDL ( Orekhov et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study design, methodology, article structure and language have been inspired by our previous studies regarding deregulation of miRNA regulatory network in lower extremities arterial disease [ 28 ] and chronic venous disease [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified dysregulations of gene expression associated with vascular cell functions, including cell differentiation, proliferation, migration, and apoptosis exhibiting modulatory function of angiogenesis, endothelial cells dysfunction and response for ischemic events and oxidative stress [ 26 , 27 , 28 , 29 , 30 , 31 ]. Alterations in expression of numerous genes are considered as potential signatures of vascular diseases including atherosclerosis [ 32 , 33 , 34 ], LEAD [ 35 , 36 , 37 ], AAA [ 38 , 39 , 40 , 41 , 42 ] and CVD [ 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, transcriptomic patterns of PBMCs subpopulations originating from patients with LEAD, AAA and CVD versus healthy subjects were previously compared and potential transcriptomic biomarkers of these diseases were proposed [ 37 , 42 , 46 ]. In the current study, pairwise comparison of gene expression profiles between LEAD, AAA and CVD were performed in order to identify transcriptomic similarities and differences of these conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation